2019
DOI: 10.1002/jcsm.12434
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of muscle wasting by glucagon‐like peptide‐1 receptor agonist in muscle atrophy

Abstract: Background Skeletal muscle atrophy is defined as a reduction of muscle mass caused by excessive protein degradation. However, the development of therapeutic interventions is still in an early stage. Although glucagon‐like peptide‐1 receptor (GLP‐1R) agonists, such as exendin‐4 (Ex‐4) and dulaglutide, are widely used for the treatment of diabetes, their effects on muscle pathology are unknown. In this study, we investigated the therapeutic potential of GLP‐1R agonist for muscle wasting and the mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
76
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 76 publications
(153 reference statements)
4
76
1
Order By: Relevance
“…Aside from the blood glucose-lowering effects, GLP-1 receptor agonists also exert beneficial effects on the skeletal muscle by increasing glucose uptake (Thompson and Kanamarlapudi, 2013), fat oxidation, and thermogenic gene expression (Choung et al, 2017). In addition, GLP-1 receptor agonist, Ex-4, imparts therapeutic effects in muscle atrophy induced by dexamethasone (Hong et al, 2019). In the present study, we investigated the effect of dulaglutide, a GLP-1 receptor agonist, on disuse-induced muscle atrophy and evaluated the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aside from the blood glucose-lowering effects, GLP-1 receptor agonists also exert beneficial effects on the skeletal muscle by increasing glucose uptake (Thompson and Kanamarlapudi, 2013), fat oxidation, and thermogenic gene expression (Choung et al, 2017). In addition, GLP-1 receptor agonist, Ex-4, imparts therapeutic effects in muscle atrophy induced by dexamethasone (Hong et al, 2019). In the present study, we investigated the effect of dulaglutide, a GLP-1 receptor agonist, on disuse-induced muscle atrophy and evaluated the underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that the exposure to exendin-4 (Ex-4) could increase glucose uptake by stimulating the 5′-AMP-activated protein kinase (AMPK) signaling pathway in rat L6 myotubes (Andreozzi et al, 2016). In addition, Ex-4 increased oxygen consumption and thermogenic gene expression in C2C12 myotubes (Choung et al, 2017) and was recently reported to exert therapeutic effects in dexamethasone-induced muscle atrophy (Hong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Ophthalmic Res 2020;63:404-412 DOI: 10.1159/000504891 causes RPE cell dysfunction or apoptosis. GLP-1 receptor agonist can inhibit oxidative stress in some cells, such as pancreatic β cells, myotube, and renal cells [18][19][20]. However, there is no evidence on whether EX4 can reduce oxidative stress-induced RPE cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we recently revealed that 24 weeks of treatment with the glucagon-like peptide-1 (GLP-1) receptor agonist, liraglutide, decreased body fat and IHL to a similar degree, but did not reduce the muscle in patients with type 2 diabetes [2]. Rather, in animal models, the GLP-1 receptor agonist and dipeptidyl peptidase-4 (DPP-4) inhibitor revealed anabolic action on skeletal muscle [3,4], and a recent report showed that DPP-4 inhibitor treatment for 1 year prevented age-associated decline of skeletal muscle as evaluated by dual-energy X-ray absorptiometry (DXA) in the patients with type 2 diabetes [5]. We also reported the effect of 24-week treatment with the DPP-4 inhibitor, sitagliptin, and the sulfonylurea, glimepiride, on body composition in Japanese overweight and obese patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%